Intra-Sentential Code Switching in Novel Cinta di dalam Gelas by Andrea Hirata - Cahaya Dwipayanti, Luh Ade Wulan; Maharani, Putu Devi (British (Jurnal Bahasa dan Sastra Inggris), 2024)
This study focuses on the use of intrasentential code-switching in the Cinta di Dalam Gelas novel by Andrea Hirata. There are two objectives of this study: to (1) identify the different levels of intrasentential switching and (2) examine the reasons that motivate it. Data gathered from the novel entitled Cinta di Dalam Gelas Novel, which was analyzed using a qualitative method. This method was applied in order to give a clear description of the data according to the theory proposed by Halliday (2004), Romaine (1989), and Hoffman (1991). The researcher found 3 types of words that appeared in intra-sentential switching used in the novel Cinta di Dalam Gelas by Andrea Hirata: nouns, adjectives, and verbs. The researcher also found a phrase in the novel: there is a noun phrase. The most common types of level of intra-sentential code-switching that were found are nouns and noun phrases, and the most common reason for code-switching found in the novel is talking about a particular topic.